The Effect Of Work Environment On Career Commitment With Job Satisfaction As A Mediation Variable On Employees Of PT Bank Syariah Indonesia KCP Pasaman Barat - Sakdiah, Halimatus; Fitia, Yuki (CV. ITTC INDONESIA, 2024)
Objectives- This study aims to analyze: (1) the influence of the work environment on career commitment (2) the influence of the work environment on job satisfaction (3) the influence of job satisfaction on career commitment (4) the influence of job satisfaction mediate the relationship between the work environment and career commitment. Methodology- This research is causal research. The population of this research is all employees of PT Bank Syariah Indonesia Kcp Pasaman Barat with a total of 40 employees and this research uses total sampling to get a population of 40 employees. The sampling technique was taken using proportional clustered simple random sampling where samples were selected in each division according to their proportions and the chance of each member of the population being in the sample was equally large. Data collection used a questionnaire with a Likert scale . Data analysis techniques use Smart PLS 4.1.0.0 software The results of data processing in this research show that: (1) the work environment has a positive and significant effect on career commitment for employees of PT Bank Syariah Indonesia Kcp West Pasaman (2) the work environment has a positive and significant effect on job satisfaction for employees of PT Bank Syariah Indonesia Kcp West Pasaman (3) job satisfaction has a positive and significant effect on career commitment among employees of PT Bank Syariah Indonesia Kcp West Pasaman (4) job satisfaction has a positive and significant mediating effect on the relationship between the work environment and career commitment among employees of PT Bank Syariah Indonesia Kcp West Pasaman. Keywords: Work Environment, Career Commitment, Job Satisfaction